GASTRIC NEUROENDOCRINE TUMOR: REVIEW AND UPDATE - DIAS,Andre Roncon (2017)
ABSTRACT Introduction: The frequency of gastric neuroendocrine tumors is increasing. Reasons are the popularization of endoscopy and its technical refinements. Despite this, they are still poorly understood and have complex management. Aim: Update the knowledge on gastric neuroendocrine tumor and expose the future perspectives on the diagnosis and treatment of this disease. Method: Literature review using the following databases: Medline/PubMed, Cochrane Library and SciELO. Search terms were: gastric carcinoid, gastric neuroendocrine tumor, treatment. From the selected articles, 38 were included in this review. Results: Gastric neuroendocrine tumors are classified in four clinical types. Correct identification of the clinical type and histological grade is fundamental, since treatment varies accordingly and defines survival. Conclusion: Gastric neuroendocrine tumors comprise different subtypes with distinct management and prognosis. Correct identification allows for a tailored therapy. Further studies will clarify the diseases biology and improve its treatment.